2016
DOI: 10.1002/jso.24225
|View full text |Cite
|
Sign up to set email alerts
|

Does the modified Glasgow Prognostic Score (mGPS) have a prognostic role in esophageal cancer?

Abstract: mGPS is associated with advanced stage but has no independent prognostic significance and does not impact on operative outcomes. Consequently, this data does not support its routine application in patient selection or prognostication. J. Surg. Oncol. 2016;113:732-737. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Dutta et al [ 32 ] suggested that mGPS plus TNM stage could predict prognosis more accurately than mGPS alone in esophageal gastric cancer. Walsh et al [ 33 ] reported that mGPS was not significantly associated with survival in resectable adenocarcinoma of the esophagus or in esophageal-gastric cancer. Similarly, mGPS appears to be of limited use as a prognostic marker in mGC.…”
Section: Discussionmentioning
confidence: 99%
“…Dutta et al [ 32 ] suggested that mGPS plus TNM stage could predict prognosis more accurately than mGPS alone in esophageal gastric cancer. Walsh et al [ 33 ] reported that mGPS was not significantly associated with survival in resectable adenocarcinoma of the esophagus or in esophageal-gastric cancer. Similarly, mGPS appears to be of limited use as a prognostic marker in mGC.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that systemic inflammatory response is a good determinant of development as well as progression of cancer . These insights led to the investigation of the GPS as a predictor in diverse surgically treated malignancies, such as colorectal cancer, esophageal cancer, and gastric cancer …”
Section: Introductionmentioning
confidence: 99%
“…8,9 These insights led to the investigation of the GPS as a predictor in diverse surgically treated malignancies, such as colorectal cancer, esophageal cancer, and gastric cancer. [10][11][12] The objective of this study is to explore the prognostic ability of GPS-based scores, the GPS, modified GPS (mGPS), and hepatic GPS (hGPS), as well as the Abe score, to predict post-transplant mortality in adult recipients with HCC, as prognostic models in a current European transplant setting. In addition to the promising results of Abe et al in living donor liver transplantation, this study should further investigate the GPS' relevance in the deceased donor setting.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to investigate the correlation between peripheral blood-derived in ammation markers and tumor prognosis [17,18]. Liu showed that CRP/Alb was an independent prognostic marker for patients with ovarian cancer [19].…”
Section: Discussionmentioning
confidence: 99%